Sentiment Analysis on Corona Virus Pandemic Using Machine Learning Algorithm - Ricky Risnantoyo; Arifin Nugroho; Kresna Mandara (Universitas Medan Area, 2020)
Corona virus outbreaks that occur in almost all countries in the world have an impact not only in the health sector, but also in other sectors such as tourism, finance, transportation, etc. This raises a variety of sentiments from the public with the emergence of corona virus as a trending topic on Twitter social media. Twitter was chosen by the public because it can disseminate information in real time and can see market reactions quickly. This research uses